Relationship between working memory and attention level using intensive game design - Tan, Rui Xuan (2019)
In the current 21st century, the type of video games with the potential of affecting human working memory and attention level increases significantly. The objective of this Final Year Project (FYP) is to develop and design an intensive video game (VG) that uses Electroencephalography (EEG) signals to control the game. In order to translate EEG signals into an effective control signal, a data recording application is developed. Thus, data extraction and classification of EEG signals were performed to find out the effective threshold of attention level. These threshold values will be implemented in the game. The game “3D Room Invasion” is created using Unity 3D. The main goal of this game is to protect the room area by shooting down all the enemies and memorising letters that is needed to pick up the power ups in order to obtain high score. A research trial was conducted with 5 participants playing the game. Results have shown that attention level high does not ensure working memory will be in its optimal state. In addition, playing intensive game will affect working memories negatively.